Comparative Analysis of the Use of LED and HPS Lights in PT. Bukit Asam - Hasibi, Rahmat Adiprasetya Al; Jamal, Agus; Surahmat, Indar; Hardiyanto, Tio; Jusman, Yessi; Arkan, Fardhan (Journal of Electrical Technology UMY, 2019)
The lamp is the main construction facility in the company that serves as a support for the activities of the economic system and mobility in the company. An analysis of the difference between the use of LED lights with HPS lamps at PT. Bukit Asam Tbk. reference is used to recommend the use of appropriate (technical) lighting equipment for industrial areas and to obtain better cumulative costs and energy savings for the company in the future. In this study using the lamp replacement method with the same lumen level comparison. The goal is that later the level of lighting produced is the same for each lamp. From the results of this study it was found that the technical use of 70W, 150W, 250W and 400W HPS lamps has an efficacy level of 84 to 123 lm / W. Whereas the 80W, 200W, 300W, 450W LED lamps are 90 lm / W and the results of the cumulative value or the total cost of operating and maintenance costs for 15 years between HPS lamps versus the LED lights that occur is that in HPS lamps the total cost incurred amounting to 20,604,230,235 rupiahs while for LED lamps it is 27,787,386,324 rupiahs which can be seen that the use of more economical lighting is HPS lamps.